2022
DOI: 10.3390/w14101553
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach for Groundwater Potential Mapping in a Fractured Semi-Arid Terrain (Kerdous Inlier, Western Anti-Atlas, Morocco)

Abstract: This study is focused on developing an approach for spatial mapping of groundwater by considering four types of factors (geological, topographical, hydrological, and climatic factors), and by using different bivariate statistical models, such as frequency ratio (FR) and Shannon’s entropy (SE). The developed approach was applied in a fractured aquifer basin (Ameln Basin, Western Anti-Atlas, Morocco), to map the spatial variation of groundwater potential. Fifteen factors (15) influencing groundwater were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…In this study, we use the AHP model with 14 factors to map the potential groundwater areas (GWPA) in the Ifni basin. This approach has yielded satisfactory results in similar basins [4,5,9,11,19,22]. Our analysis of the factors, such as those used in previous studies [4,5,10,22], revealed that certain relevant factors, such as land use, the intersection between geological lineaments and the hydrographic network, the density of the nodes, and TPI, were not considered in the model.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In this study, we use the AHP model with 14 factors to map the potential groundwater areas (GWPA) in the Ifni basin. This approach has yielded satisfactory results in similar basins [4,5,9,11,19,22]. Our analysis of the factors, such as those used in previous studies [4,5,10,22], revealed that certain relevant factors, such as land use, the intersection between geological lineaments and the hydrographic network, the density of the nodes, and TPI, were not considered in the model.…”
Section: Introductionmentioning
confidence: 78%
“…This approach has yielded satisfactory results in similar basins [4,5,9,11,19,22]. Our analysis of the factors, such as those used in previous studies [4,5,10,22], revealed that certain relevant factors, such as land use, the intersection between geological lineaments and the hydrographic network, the density of the nodes, and TPI, were not considered in the model. In discontinuous environments, aquifer recharge primarily occurs through faults and lineaments that intersect with the hydrographic network [34].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…For instance, some researchers have used probabilistic models like the frequency ratio (Ozdemir 2011;Razandi et al, 2015), logistic regression (Ozdemir 2011;Pourtaghi and Pourghasemi 2014;Pourghasemi and Beheshtirad, 2015), weights of evidence (Corsini et al, 2009;Ozdemir 2011;Lee et al, 2012;Echogdali et al, 2023), evidential belief function (Mogaji et al, 2015;Pourghasemi and Beheshtirad, 2015), certainty factor (Razandi et al, 2015), decision tree (Chenini and Mammou 2010), artificial neural network model (Lee et al, 2012), Shannon's entropy (Naghibi et al, 2015), on the whole, remote sensing and GIS are powerful tools that can quickly estimate natural resources. The methods are affordable and can be utilized to successfully explore groundwater (Faust et al, 1991;Hinton 1996;Jha et al, 2010;Benjmel et al, 2022) before utilizing more involved and expensive surveying techniques. The success of the application of remote sensing and geographic information system (GIS) techniques for mapping groundwater potential zones in various regions of the world has been reported (Madrucci et al, 2003;Jaiswal et al, 2003;Solomon and Quiel, 2006;Madrucci et al, 2008;Prasad et al, 2008;Chowdhury et al, 2009;Yeh et al, 2009;Dar et al, 2010;Dar et al, 2010;Saha et al, 2010).…”
Section: Introductionmentioning
confidence: 99%